São João Del Rei na crise da mineração: dinâmicas econômicas e populacionais (1750-1808) - Santos, Caio Cruz [UNIFESP] (2020)
The research aims to understand the construction of economic and population dynamics in the village of São João del Rei in the period 1750-1808, through both commercial relations and the evolution of the productive structure. We try to understand this process through three factors. The first is related to the relationship between the public and the private, that is, through land concessions, licenses granted and the efforts of the chamber in a certain direction, this relationship allows visualizing both the public structure of the time and the daily life of society for the various economic areas, showing what society demanded from the public entity. The second refers to the understanding of market relations in the village of São João del Rei, embodied in the creation and expansion of stores, sales of dry and wet products and greengrocers. The last comprises the formation of Sanjoanense wealth in this period, which allows to understand the productive structure of the region and its transformations. It is concluded that dualist regions like São João del Rei, did not stand out for the size of their - transit through this unstable period of the Captaincy. Thus, with the gold decay in Minas, the accumulation of capital resulting from gold mining, the abundance of fertile land in a politically organized Comarca Head and the proximity to the urban center of Rio de Janeiro, allowed the town to organize itself as a supply center of this region and do not go into economic decline.